An iron-based metal-organic framework nanoplatform for enhanced ferroptosis and oridonin delivery as a comprehensive antitumor strategy - Mengru Cai; Tingting Fu; Rongyue Zhu; Panxiang Hu; Jiahui Kong; Shilang Liao; Yuji Du; Yongqiang Zhang; Changhai Qu; Xiaoxv Dong; Xingbin Yin; Jian Ni (Elsevier, 2024)
Ferroptosis is a recently discovered pathway for regulated cell death pathway. However, its efficacy is affected by limited iron content and intracellular ion homeostasis. Here, we designed a metal-organic framework (MOF)-based nanoplatform that incorporates calcium peroxide (CaO2) and oridonin (ORI). This platform can improve the tumor microenvironment and disrupt intracellular iron homeostasis, thereby enhancing ferroptosis therapy. Fused cell membranes (FM) were used to modify nanoparticles (ORI@CaO2@Fe-TCPP, NPs) to produce FM@ORI@CaO2@Fe-TCPP (FM@NPs). The encapsulated ORI inhibited the HSPB1/PCBP1/IREB2 and FSP1/COQ10 pathways simultaneously, working in tandem with Fe3+ to induce ferroptosis. Photodynamic therapy (PDT) guided by porphyrin (TCPP) significantly enhanced ferroptosis through excessive accumulation of reactive oxygen species (ROS). This self-amplifying strategy promoted robust ferroptosis, which could work synergistically with FM-mediated immunotherapy. In vivo experiments showed that FM@NPs inhibited 91.57% of melanoma cells within six days, a rate 5.6 times higher than chemotherapy alone. FM@NPs were biodegraded and directly eliminated in the urine or faeces without substantial toxicity. Thus, this study demonstrated that combining immunotherapy with efficient ferroptosis induction through nanotechnology is a feasible and promising strategy for melanoma treatment.